A rapid quantitative fluorescence-based bioassay to study allelochemical interactions from Alexandrium minutum. (November 2018) - Long, Marc; Tallec, Kévin; Soudant, Philippe; Lambert, Christophe; Le Grand, Fabienne; Sarthou, Géraldine; Jolley, Dianne; Hégaret, Hélène
Abstract: Harmful microalgal blooms are a threat to aquatic organisms, ecosystems and human health. Toxic dinoflagellates of the genus Alexandrium are known to produce paralytic shellfish toxins and to release bioactive extracellular compounds (BECs) with potent cytotoxic, hemolytic, ichtyotoxic and allelopathic activity. Negative allelochemical interactions refer to the chemicals that are released by the genus Alexandrium and that induce adverse effects on the physiology of co-occurring protists and predators. Releasing BECs gives the donor a competitive advantage that may help to form dense toxic blooms of phytoplankton. However BECs released by Alexandrium minutum are uncharacterized and it is impossible to quantify them using classical chemical methods. Allelochemical interactions are usually quantified through population growth inhibition or lytic-activity based bioassays using a secondary target organism. However these bioassays require time (for growth or microalgal counts) and/or are based on lethal effects. The use of pulse amplitude modulation (PAM) fluorometry has been widely used to assess the impact of environmental stressors on phytoplankton but rarely for allelochemical interactions. Here we evaluated the use of PAM and propose a rapid chlorophyll fluorescence based bioassay to quantify allelochemical BECs released from Alexandrium minutum . We used the ubiquitous diatom Chaetoceros muelleri as a target species. The bioassay, based on sub-lethal effects, quantifies allelochemical activity from different samples (filtrates, extracts in seawater) within a short period of time (2 h). This rapid bioassay will help investigate the role of allelochemical interactions in Alexandrium bloom establishment. It will also further our understanding of the potential relationship between allelochemical activities and other cytotoxic activities from BECs. While this bioassay was developed for the species A. minutum, it may be applicable to other species producing allelochemicals and may provide further insights into the role and impact of allelochemical interactions in forming dense algal blooms and structuring marine ecosystems. Graphical abstract: Image 1 Highlights: We developed a fast bioassay to screen Alexandrium bioactive extracellular compounds. The rapid quantification of allelopathic BECs is based on PAM fluorometry. This will help investigating links between allelo-, ichtyo-, hemo- and cytotoxicity. The bioassay will ease chemical identification of unknown bioactive compounds. The bioassay could be applied to algal cultures, extracts and environmental samples. Abstract : The study proposes a new protocol that allows a fast and easy quantification of unknown bioactive extracellular compounds with cytotoxic activities.